2013
DOI: 10.3168/jds.2013-6789
|View full text |Cite
|
Sign up to set email alerts
|

A first step toward genomic selection in the multi-breed French dairy goat population

Abstract: The objectives of this study were to describe, using the goat SNP50 BeadChip (Illumina Inc., San Diego, CA), molecular data for the French dairy goat population and compare the effect of using genomic information on breeding value accuracy in different reference populations. Several multi-breed (Alpine and Saanen) reference population sizes, including or excluding female genotypes (from 67 males to 677 males, and 1,985 females), were used. Genomic evaluations were performed using genomic best linear unbiased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 37 publications
6
83
8
1
Order By: Relevance
“…Dominance deviations are by definition included in YD, but not in DYD. The variance of e YD is σE2 and of e DYD i (the i ‐th element of e DYD ) is 2σA2+4(normalσD2+normalσE2)ndaui (Carillier et al., ). n dau i is the number of daughters’ YD included in the calculation of the i ‐th DYD.…”
Section: Methodsmentioning
confidence: 99%
“…Dominance deviations are by definition included in YD, but not in DYD. The variance of e YD is σE2 and of e DYD i (the i ‐th element of e DYD ) is 2σA2+4(normalσD2+normalσE2)ndaui (Carillier et al., ). n dau i is the number of daughters’ YD included in the calculation of the i ‐th DYD.…”
Section: Methodsmentioning
confidence: 99%
“…However, so far, only attempts in France (Carillier et al . , ) and the UK (Mucha et al . ) are being undertaken to implement genomic selection in dairy goat breeding programs, as the global breeding industry is not as well established when compared with that for dairy cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic evaluation is already used routinely in many dairy cattle breeding programs and is expected to be implemented in the near future in other species. Recent studies in sheep and goats reported that the genomic evaluation of young males was more accurate than polygenic, pedigree-based evaluation (Daetwyler et al, 2012;Duchemin et al, 2012;Baloche et al, 2013;Carillier et al, 2013 and2014).…”
Section: Introductionmentioning
confidence: 99%